Animal shelter management of feline leukemia virus and feline immunodeficiency virus infections in cats - Dezubiria, Paola; Amirian, E. Susan; Spera, Keegan; Crawford, P. Cynda; Levy, Julie K. (Frontiers in Veterinary Science, 2023)
Approximately 5% of cats in animal shelters in the United States test positive for either feline leukemia virus (FeLV) or feline immunodeficiency virus (FIV), which translates to more than 100,000 positive cats managed by shelters each year. Little is known about the current status of retroviral management in animal shelters, particularly in regions burdened by chronic pet overpopulation and high shelter admissions, such as the southern United States. The purpose of this study was to describe feline retroviral management in Florida shelters. Shelters were surveyed on practices including selection of cats for testing, diagnostic techniques, and outcome options for cats with positive test results. Responses were received from 139 of 153 animal shelters known to admit cats, including 55 municipal shelters (39%), 70 private shelters (50%), and 14 private shelters with municipal contracts (10%). A total of 115 shelters (83%) performed at least some testing, most using combination point-of-care devices for simultaneous FeLV antigen and FIV antibody screening. Of shelters that performed any testing, 56 (40%) tested all cats for FeLV and 52 (37%) tested all cats for both FeLV and FIV. The most common reason for testing was screening adoptable cats (108 shelters; 77%) and cats available for transfer to other organizations (78; 56%). Testing cats in trap-neuter-return/return-to-field programs was least common (21; 15%). Most common outcome options for positive cats included adoption (74; 64%), transfer (62; 54%), and euthanasia (49; 43%). Euthanasia following a positive test result was more common for cats with FeLV (49; 43%) than for cats with FIV (29; 26%) and was more common in municipal shelters, rural shelters, shelters taking in <500 cats a year, and shelters with overall live outcome rates for cats <70%. Although Florida shelter compliance with national guidelines for identification and management of FeLV and FIV positive cats was variable, most had live outcome options for at least some of their cats with positive test results. Increased access to training and practical programmatic tools may help more shelters implement cost-effective testing protocols, reduce risk for transmission to other cats, and support the best outcomes for this vulnerable population of cats.